INFLUÊNCIA DO PERFIL DE CONSUMO ATUAL DE GLP NO DIMENSIONAMENTO DA CENTRAL DE GÁS PREDIAL - Faccio, Thomás Denis; Scortegagna, Vinicius; Arruda, Winícius Morais; Cartana, Vera Maria; Fiori, Simone; Ferreira, Matheus de Conto; Gil, Anelise Sertoli (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In residential buildings with indirect gas distribution system, the supply of each housing unit is carried out by liquefied petroleum gas (LPG), and it is necessary for the engineer to dimension the volume of the LPG tanks. The sizing of the required volume depends on the estimation of appliances that consume gas in each unit, which follows values established by standards and technical instructions. The projects are increasingly optimized and the evolution of the appliances have modified the consumption pattern of the buildings individually. Therefore, it is important to know which features should be considered in the optimized sizing, avoiding additional costs. This work aims to verify the consumption of LPG through real data, number of inhabitants, existing LPG consuming devices, as well as bibliographical researches of the real consumption of other buildings, confronting with the sizing that is commonly followed by the civil engineers. The study shows the importance of updating the parameters used in the calculations, showing that in the proposed situations, the methodologies present values of oversizing in buildings of middle social class and in situations where the social class is high the values of dimensioning are presented closer to the real consumption.